Hummingbirds [videorecording (DVD)] : magic in the air - Abraham, F. Murray (Distributed by Questar, Inc., 2010)
Hummingbirds are the tiniest of birds, yet they are some of the toughest creatures on the planet. Using cameras able to capture over 500 images a second, the hummingbirds' magical world can finally be seen and appreciated. Nature reveals their stunning abilities as they have never been seen before. Narrated by F. Murray Abraham.